Risk of peri-intubation adverse events during emergency department intubation of overdose patients: a national emergency airway registry (near) analysis. (2nd December 2022) - Kunzler, Nathan M.; Cole, Jon B.; Driver, Brian E.; Carlson, Jestin; April, Michael; Brown, Calvin A.
Abstract: Background: More than 20, 000 emergency department (ED) patients undergo intubation for overdose each year. While the characteristics of patients intubated for overdose and poisoning are well described, little is known about the intubation outcomes of overdose patients in the ED. Objectives: We quantify the frequency of peri-intubation adverse events for patients intubated in the ED for overdose, and determine whether first attempt success without adverse events differs between patients intubated for overdose and patients intubated for other reasons. Methods: We analyzed data from the National Emergency Airway Registry (NEAR), a prospective multicenter registry of ED intubations collected from an international network of 22 academic and community hospitals. We included patients 14 years and older whose first attempt was oral intubation, with data entered into NEAR between 1 January 2016 and 31 December 2018. The primary outcome was successful intubation on the first attempt. We used multivariable logistic regression to determine whether indication was independently associated with successful intubation on the first attempt after adjusting for age, gender, obesity, initial impression of difficult airway, presence of difficult airway characteristics, and use of video laryngoscopy. Secondary outcomes included successful intubation on the first attempt without adverse events, the occurrence of rescue surgical airways, and the occurrence of adverse events. Adverse events included hypoxemia, hypotension, peri-intubation cardiac arrest, bradycardia, mechanical injury to oral or airway structures, vomiting, tachydysrhythmia, esophageal intubation, laryngospasm, and pneumothorax. Results: We analyzed 17, 984 patients, including 1, 983 (11%) intubated for overdose, and 16, 001 (89%) intubated for other indications. Patients intubated for overdose were younger (median age 38 vs 55 years), were less frequently obese (26% vs 34%), and fewer had difficult airway characteristics (38% vs 53%). Overdose patients were more likely to have preoxygenation performed (45% vs 35%), more likely to have apenic oxygenation (39% vs 31%), and more likely to have bougie used (33% vs 17%). First attempt success was 90.5% in patients intubated for overdose and 87.5% in patients intubated for other reasons (absolute difference 3.0%; 95% CI: −1.3 to 7.3). First attempt success without adverse events was higher in overdose patients (85.0%) compared to other patients (78.7%) (absolute difference, 6.3%; 95% CI 1.0 to 11.7%). Overdose patients experienced significantly less hypotension (1.5% vs 4.1%), and tended to have fewer adverse events overall. Multivariable model results were consistent with the unadjusted results including no difference in first pass success (adjusted odd ratio 1.02 [95% CI 0.86–1.23]). There was a higher first pass success without complication in patients intubated for overdose (adjusted odds ratio 1.23; 95% CI 1.07 to1.43). Conclusion: For patients in whom the primary indication for intubation is overdose there is an increased chance of first attempt success without adverse event.